2009
DOI: 10.1002/ptr.3035
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis inhibition by a lichen compound olivetoric acid

Abstract: Lichens have been used in folk medicine for centuries and are symbiotic organisms of fungi and algae that produce unique secondary metabolites. Olivetoric acid is one of these secondary metabolites. In the present study, the effect of olivetoric acid isolated from acetone extract of the lichen Pseudevernia furfuracea (var. ceratea) on angiogenesis was evaluated. It displayed potent anti-angiogenic activities in vitro: inhibited proliferation of rat adipose tissue endothelial cells (RATECs) and disrupted endoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
0
37
0
2
Order By: Relevance
“…Certain lichen secondary compounds (ca. 1000 presently known) derived from fungal metabolism have antimicrobial, antiviral, antiprotozoal, antiproliferative, antitumor, antiinflammatory, anti-pyretic, analgesic, photoprotective, enzyme inhibitory and anti-angiogenic properties [4][5][6][7][8]. Usnic acid, a dibenzofuran derivative, is one of the most frequent and most studied lichen metabolites [9].…”
Section: Introductionmentioning
confidence: 99%
“…Certain lichen secondary compounds (ca. 1000 presently known) derived from fungal metabolism have antimicrobial, antiviral, antiprotozoal, antiproliferative, antitumor, antiinflammatory, anti-pyretic, analgesic, photoprotective, enzyme inhibitory and anti-angiogenic properties [4][5][6][7][8]. Usnic acid, a dibenzofuran derivative, is one of the most frequent and most studied lichen metabolites [9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, 1050 secondary metabolites are known which are unique to lichens (Stocker-Worgotter, 2008; Verma & Behera, 2015). Bioactivity studies on lichen metabolites reported in recent years indicate their therapeutic potential in terms of natural antioxidants, antimicrobial, anticancer, probiotic, anti-angiogenic, and cardiovascular protective agents Gaikwad et al, 2014;Koparal et al, 2010;Mahadik et al, 2011;Srivastava et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The latest ones in these activities have been anticancer, antimicrobial and antioxidant. Koparal et al (2010) investigated antiangiogenic activity of OLA isolated from P. furfuracea and reported that reduction in endothelial cells occurred as OLA broke structure of the actin cytoskeleton. Inhibitory activities of bacteria growth of OLA were reported by some researchers (Türk et al 2006;Mitrović et al 2014).…”
Section: Discussionmentioning
confidence: 99%